Passenger satisfaction of public transportation and its sustainable development in Malaysia - Chua, Esther Yu Jie; Chan, Kristal Hwa Ping; Wong, Choi Yen (2020)
The sustainable development is often overlooked by Malaysia whereas in developed countries, public transportation has been their option for a better nation. Since Malaysia are trying to increase their status to developed countries, Malaysia should look into providing a better and comfortable public transportation and create an environment to increase productivity. Therefore, this study is to examine the influence of service quality, timeliness, value of money and environmental attitude towards satisfaction of public transportation. Self-administered questionnaire was distributed through google form targeting people in Greater Kuala Lumpur using the stratified random sampling techniques. 347 response were receive giving a response rate of 99% Multiple Linear Regression were performed using Statistical Package for the Social Sciences (SPSS). The result indicate that service quality, timeliness and value of money have significant influence on passenger satisfaction whereas environmental attitude have insignificant relationship on passenger satisfaction.